Grandmothers’ knowledge positively influences maternal knowledge and infant and young child feeding practices - Karmacharya, Chandni; Cunningham, Kenda; Choufani, Jowel; Kadiyala, Suneetha (Cambridge University Press, 2017)
To examine associations between grandmothers’ knowledge and infant and young child feeding (IYCF) practices and to test whether the associations are independent of or operate via maternal knowledge.Cross-sectional household survey data from households with a child under 5 years (n4080). We used multivariate regression analyses, adjusted for child, maternal, grandmother and household characteristics, and district-level clustering, to test associations between grandmothers’ knowledge and IYCF practices for children aged 6–24 months living with a grandmother. We used causal mediation to formally test the direct effect of grandmothers’ knowledge on IYCF practicesv. maternal knowledge mediating these associations.Two hundred and forty rural communities, sixteen districts of Nepal.Children aged 6–24 months (n1399), including those living with grandmothers (n748).We found that the odds of optimal breast-feeding practices were higher (early breast-feeding initiation: 2·2 times,P=0·002; colostrum feeding: 4·2 times,P<0·001) in households where grandmothers had correct knowledgev. those with incorrect knowledge. The same pattern was found for correct timing of introduction of water (2·6), milk (2·4), semi-solids (3·2), solids (2·9), eggs (2·6) and meat (2·5 times; allP<0·001). For the two pathways we were able to test, mothers’ correct knowledge mediated these associations between grandmothers’ knowledge and IYCF practices: colostrum feeding (b=10·91,P<0·001) and the introduction of complementary foods (b=5·18,P<0·001).Grandmothers’ correct knowledge translated into mothers’ correct knowledge and, therefore, optimal IYCF practices. Given grandmothers’ influence in childcare, engagement of grandmothers in health and nutrition interventions could improve mothers’ knowledge and facilitate better child feeding.